Effect of initial COVID-19 outbreak during first trimester on pregnancy outcome in Wuxi, China - Yun Liu; Ming Dai; Shaidi Tang (BMC, 2022)
Abstract Background A hospital-based retrospective study was conducted to examine the effect of initial COVID-19 outbreak during first trimester on pregnancy outcome in Wuxi, China. Methods Women who delivered children at our hospital during June 2020 to July 2020 (control group), and October 2020 to December 2020 (exposure group) were recruited in the present study. All of the participants were not infected with COVID-19. The last menstrual period (LMP) of the exposure group was between January 24th, 2020 and March 12th, 2020, whilst in the control group, the LMP was between May 12th and October 31st, 2019. Results There were 1,456 women in the exposure group and 1,816 women in the control group. Women in the exposure group were more susceptible to hypertension during pregnancy (HDP, P = 0.004, OR[95%CI] = 1.90[1.22-2.95]) and gestational diabetes mellitus (GDM, P = 0.008, OR[95%CI] = 1.31[1.08-1.60]) compared to those in the control group. Mothers diagnosed with HDP were more likely to deliver premature infants, leading to a higher rate of low birth weight (all P < 0.05). The other common outcomes of pregnancy showed no statistical differences between the two groups. Conclusions The initial COVID-19 outbreak might increase the incidence rates of HDP and GDM among pregnant women whose first trimesters were during that period, resulting in higher percentages of premature delivery and low birth weight. These results should be confirmed by studies from other hospitals or cities.